How to Succeed in Your Social Science Degree. - Arksey, Hilary (SAGE Study Skills Series., 2007)
This book takes a clear-eyed approach to the challenges of university life, offers realistic advice and demonstrates how to acquire transferable skills with a view to future employability. Topics covered include: owhat employers want;. ohow educational performance can be maximized;. ohow to maximize powers of expression;. ohow to analyze data;. owhat to do and avoid doing in writing a dissertation.